Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1038/sj.bdj.4807777
|View full text |Cite
|
Sign up to set email alerts
|

Permanent damage to inferior alveolar and lingual nerves during the removal of impacted mandibular third molars. Comparison of two methods of bone removal

Abstract: Injuries to the inferior alveolar or lingual nerve are recognised complications of third molar surgery. In a prospective study, permanent damage was found to be significantly related to bone removal using a surgical drill. The Howarth periosteal elevator may not provide adequate protection to the lingual nerve when a surgical drill is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
2
9

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 0 publications
1
35
2
9
Order By: Relevance
“…This was also the case when labial and lingual nerve damage was considered separately. This is perhaps surprising, though previous studies [2][3][4][5] have found that nerve damage reflected surgical technique more than anatomical position of the tooth.…”
Section: Discussioncontrasting
confidence: 40%
“…This was also the case when labial and lingual nerve damage was considered separately. This is perhaps surprising, though previous studies [2][3][4][5] have found that nerve damage reflected surgical technique more than anatomical position of the tooth.…”
Section: Discussioncontrasting
confidence: 40%
“…(7)(8)(9)(10) Bu çalışmada amaç gömülü 3. molar diş cerrahisinde anksiyete düzeyini düşürmek için uygulanan midazolam ile kombine edilen fentanil ve tramadolün anksiyete ve postoperatif ağrı üzerine etkilerinin karşılaştırılmasıdır.…”
Section: Discussionunclassified
“…Algunos autores han mostrado un 13% de parestesia en pacientes intervenidos para extracción de terceros molares con uso de retractores, aunque esta parestesia no fue permanente (18). En aquellos casos en los que no se emplearon retractores para apartar el nervio, mostraron un 3,2% de incidencia de daño del nervio, siendo un 2% permanente.…”
Section: Región Posterior De La Mandíbulaunclassified
“…En aquellos casos en los que no se emplearon retractores para apartar el nervio, mostraron un 3,2% de incidencia de daño del nervio, siendo un 2% permanente. Todos los casos de daño permanente o irreversible del nervio estaban asociados con el uso de fresas en la tabla lingual (18). Otros estudios han mostrado que a pesar del daño transitorio que pueden causar los retractores linguales durante la cirugía de terceros molares, se sugiere su uso de manera rutinaria para la cirugía de extracción de terceros molares, ya que no se va visto afectación de manera permanente.…”
Section: Región Posterior De La Mandíbulaunclassified